Assessment of pediatric obstructive sleep apnea using a drug‐induced sleep endoscopy rating scale. (17th January 2016) - Lam, Derek J.; Weaver, Edward M.; Macarthur, Carol J.; Milczuk, Henry A.; O'Neill, Eleni; Smith, Timothy L.; Nguyen, Thuan; Shea, Steven A.
Abstract : Objectives/Hypothesis: Assess the reliability of a Sleep Endoscopy Rating Scale (SERS) and its relationship with pediatric obstructive sleep apnea (OSA) severity. Study Design: Retrospective case series of pediatric patients who underwent drug‐induced sleep endoscopy (DISE) at the time of surgery for OSA from January 1, 2013 to May 1, 2014. Methods: Three blinded otolaryngologists scored obstruction on DISE recordings as absent (0), partial (+1), or complete (+2) at six anatomic levels: nasal airway, nasopharynx, velopharynx, oropharynx, hypopharynx, and arytenoids. Ratings were summed for a SERS total score (range, 0–12). Reliability was calculated using a κ statistic with linear weighting. SERS ratings and obstructive apnea‐hypopnea index (OAHI) were compared using Spearman correlation. A receiver operating characteristic (ROC) analysis determined the ability of the SERS total score to predict severe OSA (OAHI >10). Results: Thirty‐nine patients were included (mean age, 8.3 ± 5.1 years; 36% obese; mean OAHI, 19.1 ± 23.7). Intrarater and inter‐rater reliability was substantial‐to‐excellent (κ = 0.61‐0.83) and fair‐to‐substantial (κ = 0.33‐0.76), respectively. Ratings correlated best with OAHI for the oropharynx ( r = 0.54, P = .02), hypopharynx ( r = 0.48, P = .04), and SERS total score ( r = 0.75, P = .002). In ROC analysis, a SERS total score ≥6 demonstrated sensitivity/specificity of 81.8%/87.5%, respectively, and correctly classified 84% of patients. Conclusions: The SERS can be applied reliably in children undergoing DISE for OSA. Ratings of the oropharynx, hypopharynx, and SERS total score demonstrated significant correlation with OSA severity. A SERS total score ≥6 was an accurate predictor of severe OSA. Level of Evidence: 4. Laryngoscope, 126:1492–1498, 2016